Immune Response in Severe and Non-Severe Coronavirus Disease 2019 (COVID-19) Infection: A Mechanistic Landscape - Mukund, Kavitha; Nayak, Priya; Ashokkumar, Chethan; Rao, Sohail; Almeda, Jose; Betancourt-Garcia, Monica M.; Sindhi, Rakesh; Subramaniam, Shankar (Frontiers in Immunology, 2021)
Mechanisms underlying the immune remodeling and severity response in coronavirus disease 2019 (COVID-19) are yet to be fully elucidated. Our comprehensive integrative analyses of single cell RNA sequencing (scRNAseq) data from four published studies, in patients with mild/moderate and severe infections, indicate a robust expansion and mobilization of the innate immune response and highlight mechanisms by which low-density neutrophils and megakaryocytes play a crucial role in the crosstalk between lymphoid and myeloid lineages. We also document a marked reduction of several lymphoid cell types, particularly natural killer cells, mucosal associated invariant T (MAIT) and gamma-delta T (γδT) cells and a robust expansion and extensive heterogeneity within plasmablasts, especially in severe COVID-19 patients. We confirmed the changes in cellular abundances for certain immune cell-types within a new patient cohort. While the cellular heterogeneity in COVID-19 extends across cells in both lineages, we consistently observe certain subsets that respond more potently to interferon type I (IFN-I) and display increased cellular abundances across the spectrum of severity, compared to healthy. However, we identify these expanded subsets to have a more muted response to IFN-I within severe disease compared to non-severe. Our analyses further highlight aggregation potential of the myeloid subsets particularly monocytes in COVID-19. Finally, we provide detailed mechanistic insights into the interaction between lymphoid and myeloid lineages which contributes to the multisystemic phenotype of COVID-19, distinguishing severe from non-severe responses.